PENGARUH KONFLIK PERAN GANDA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PT INFINEON TECHNOLOGIES BATAM: Bahasa Indonesia - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to analyze the effect of dual role conflict and all emotional intelligence on the performance of women employees. This research was conducted in PT Infineon Technologies Batam. The study population was women employees are encouraged FOL department at PT Infineon Technologies Batam. The sample in this study of 122 respondents to make use probability sampling method is simple random sampling. The independent variable in this study is a double role conflict and emotional intelligence, while the dependent variable is the performance of employees. The results of this study indicate that the dual role conflict and emotional intelligence significantly affect the performance of women employees. Partially dual role conflict does not significantly affect the performance of women employees, while emotional intelligence on the performance of women at the significance level of less than 0.05 or 5%.